Analisis Tingkat Kepuasan Petani Terhadap Ketersediaan Pupuk Subsidi dan Dampak dalam Produksi (Studi Kasus Petani Tanaman Pangan Kecamatan Teluk Sampit) - Pakpahan, Sartika; Manihuruk, Ekamonika (Universitas Galuh, 2025)
Teluk Sampit District in East Kotawaringin Regency holds significant potential in the agricultural sector, particularly in supporting national food security. This study aims to measure farmers' satisfaction with the availability of subsidized fertilizers, analyze the impact of fertilizer availability on agricultural productivity, and evaluate the relationship between farmers' satisfaction and crop productivity. The research employs descriptive analysis and multiple linear regression, with data collected through questionnaires administered to 286 farmers who receive subsidized fertilizers. The results indicate that farmers in Teluk Sampit are generally satisfied with the type, price, and quality of the fertilizers; however, complaints regarding the timeliness and quantity of distribution were also noted. Subsidized fertilizers have been shown to have a positive effect on agricultural production, particularly in the food crop subsector. Based on the Customer Satisfaction Index (CSI), the level of farmers' satisfaction is categorized as